OP0025 FENEBRUTINIB COMPARED TO PLACEBO AND ADALIMUMAB IN PATIENTS WITH INADEQUATE RESPONSE TO EITHER METHOTREXATE THERAPY OR PRIOR TNF THERAPY: PHASE 2 STUDY. (June 2019) - Cohen, Stanley; Tuckwell, Katie; Katsumoto, Tamiko R.; Zhao, Rui; Lee, Chin; Berman, Alberto; Damjanov, Nemanja; Fedkov, Dmytro; Jeka, Sławomir; Genovese, Mark C.
Abstract : Background: Fenebrutinib (GDC-0853, FEN) is a small molecule inhibitor of Bruton's Tyrosine Kinase (BTK) that is orally administered, highly selective, non-covalent, and reversible. Objectives: This study evaluated the efficacy and safety of FEN compared with placebo (PBO) and adalimumab (ADA), in combination with background methotrexate (MTX), in patients (pts) with rheumatoid arthritis (RA). Methods: This multicenter, randomized, double-blind Phase 2 study included pts with moderate-to-severe active RA with an inadequate response to MTX (MTX-IR, Cohort 1) or TNF inhibitors (TNF-IR, Cohort 2). Cohort 1 pts were randomized to FEN at 50 mg QD (FEN-50), 150 mg QD (FEN-150), 200 mg BID (FEN-200), 40 mg ADA injections SC Q2W, or PBO. Cohort 2 pts were randomized to FEN-200 or PBO. Key efficacy endpoints evaluated the proportion of pts with an ACR50 response at Week 12 (W12), comparing FEN doses to PBO (both cohorts) and to ADA (Cohort 1). Results: Cohort 1 (FEN-50, n=40; FEN-150, n=109; FEN-200, n=110; PBO, n=110; ADA, n=111) and Cohort 2 (FEN-200, n=48; PBO, n=50) demographics and disease characteristics were balanced, and ∼90% of pts per arm completed the study. In Cohort 1, ACR50 response rates increased with increasing FEN dose (18%, 28%, and 35% for FEN-50, FEN-150, and FEN-200, respectively). FEN-150 (28%, p=0.0164) and FEN-200 (35%, p=0.0003) were superior to PBO (15%), and numerically similar to ADA (36%). In Cohort 2, the response for FEN-200 was higher than PBO (25% vs. 12%) (Table 1). Adverse events (AEs) were generally balanced across Cohort 1; there were 9 serious AEs in 7 pts and one death in the FEN-200 group. In Cohort 2, more pts in the PBO arm reported AEs, and no serious AEs were reported. Conclusion: FEN demonstrated higher efficacy rates than PBO for ACR50 at W12 in both MTX-IR and TNF-IR populations, and was similar to ADA in MTX-IR pts. The overall safety profile of FEN was acceptable. Disclosure of Interests: Stanley Cohen Grant/research support from: AbbVie, Amgen Inc., AstraZeneca, Biogen-IDEC, Bristol Meyer Squibb, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Merck, and Roche, Consultant for: Abbvie, Amgen, AstraZeneca, Biogen-IDEC, Bristol Meyer Squibb, Genentech, Janssen, Lilly, Novartis Pfizer, Merck and Roche, Katie Tuckwell Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Tamiko R. Katsumoto Shareholder of: Genentech, Inc., Consultant for: Roche/Genentech, Principia Biopharma, Abbvie, Employee of: Former employee of Genentech, Inc., Rui Zhao Shareholder of: Genentech, Inc., Employee of: Genentech, Inc., Chin Lee Shareholder of: Roche/Genentech and of Eli Lilly & Co., Employee of: Genetech, Inc. and Eli Lilly & Co., Alberto Berman Grant/research support from: Grants/research support: Roche/Genentech, Bristol-Myers Squibb, Merck Serono, AbbVie, Amgen, Eli Lilly, Janssen, Nemanja Damjanov Grant/research support from: AbbVie, Pfizer and Roche, Consultant for: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Speakers bureau: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Dmytro Fedkov Grant/research support from: MSD, AbbVie, ProPharma, Laboratoires Expanscience; Consultant for: MSD, AbbVie, ProPharma, Laboratoires Expanscience; Speakers bureau: Janssen, Sławomir Jeka: None declared, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm